Acid tolerance response of Salmonella during simulated chilled beef storage and its regulatory mechanism based on the PhoP/Q system. (May 2021) - Lang, Chenxiao; Zhang, Yimin; Mao, Yanwei; Yang, Xiaoyin; Wang, Xiaoyun; Luo, Xin; Dong, Pengcheng; Zhu, Lixian
Abstract: To investigate the persistence of acid tolerance response (ATR) and the regulatory mechanism during chilled storage, Salmonella ATCC 14028 and the △phoP mutant were acid adapted and then incubated in meat extract at 4 °C for 24 days as simulated beef storage. The bacterial population, D values and expression of PhoP/PhoQ linked genes of both strains were determined at 6-day intervals. Although a mild suppression effect on the D values of adapted Salmonella was found during the long-time storage in meat extract at 4 °C, the D value of adapted strains was significantly higher than non-adapted strains, indicating the persistence of ATR during the whole aging and distribution of beef posing a threat to food safety. The fact that low temperature inhibits the formation of ATR at the early adapted stage emphasizes the importance of keeping a low-temperature environment during slaughter. An interaction between the acidic adaptation and phoP gene on D values was found and the expression levels of adiA, adiY, cadA and cadB genes was significantly reduced in the △phoP mutant, suggesting that PhoP/Q system plays an important role in the ATR by sensing the pH and regulating lysine and arginine decarboxylation directly or indirectly. Highlights: Acid tolerance response (ATR) of Salmonella sustained for 24 days in the meat extract. Low temperature (4 °C) inhibits the expression of ATR. Interaction effect between the phoP gene and acidic adaptation on the ATR was found. PhoP/PhoQ promotes acid tolerance of Salmonella by the regulation of amino acid metabolism system.